Metastatic Ductal Carcinoma of the Mammary Diagnosed During Pregnancy: A Case Report - Kazım Gezginç; Rengin Karataylı; Fatma Yazıcı Yılmaz; Hüseyin Görkemli; Çetin Çelik (Medical Network, 2012)
To report a case of an invasive ductal carcinoma of the mammary diagnosed in the 3rd trimester of pregnancy. A 30-year-old woman, with gravidity 2, parity 1 and presenting at the 29th week of gestation was referred to our centre with the complaint of a palpable hard breast mass. Examination of the mammary revealed few 0,5-1 cm hard mobile mass. The ultrasonography revealed heterogenous hypoechoic noduler lesions sized 7x5mm and 6x4 mm at the level of 11 o'clock, 16x12 mm at the level of 8 o'clock, 6,5x5 mm at the level of 7 o'clock, 6x7 mm at the level of 6 o'clock on the right mammary. We performed biopsies from the leisons and the pathology result was reported as inflammatory type of ductal carcinoma. Abdominal ultrasonography revealed a 1,5x1,6 cm of hypoechoic lesion with undistinguished borders. Radical mastectomy after a neoadjuvant chemotherapy was planned. A course of adriamycin+cyclophosphamide therapy was administered. At the 33rd week of gestation caesarean section was performed because of oligohydramniosis. Modified radical right mastectomy following neoadjuvant chemotherapy was performed after delivery. After the operation cisplatin+etoposide+5-fluorouracil therapy and radiotherapy was adminstered. In her 13rd month of follow up gemsitabin+zolandronik acid therapy was started because of bone metastasis. After 18 months with the detection of the carcinoma in the left breast left mastectomy was performed. The patient is still being followed up and the first course of cisplatin+etoposid+5-fluorouracil chemotherapy has been given. The prognosis of the breast cancer in pregnancy is same with those in non pregnant. But the physiological changes of the breast during pregnancy can delay the diagnosis and the patients can be detected in late stages.